2004
DOI: 10.2337/diacare.27.10.2348
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cell Function and Immune Responses to Insulin After Administration of Intranasal Insulin to Humans At Risk for Type 1 Diabetes

Abstract: OBJECTIVE -Mucosal administration of insulin retards development of autoimmune diabetes in the nonobese diabetic mouse model. We conducted a double-blind crossover study in humans at risk for type 1 diabetes to determine if intranasal insulin was safe, in particular did not accelerate ␤-cell destruction, and could induce immune effects consistent with mucosal tolerance. RESEARCH DESIGN AND METHODS-A total of 38 individuals, median age 10.8 years, with antibodies to one or more pancreatic islet antigens (insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 41 publications
5
112
0
4
Order By: Relevance
“…There is now evidence that intranasal (pro)insulin peptide administration induces pathogenic CTL [42]. The possibility of inducing pathogenic CTL should therefore be considered in ongoing trials with intranasal insulin, although a pilot study in children receiving intranasal insulin found a decline in humoral and proliferative T-cell responses to insulin [62], thus suggesting that intranasal insulin induces mucosal tolerance. We propose that in intranasal protocols, peptides rather than protein should be administered.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…There is now evidence that intranasal (pro)insulin peptide administration induces pathogenic CTL [42]. The possibility of inducing pathogenic CTL should therefore be considered in ongoing trials with intranasal insulin, although a pilot study in children receiving intranasal insulin found a decline in humoral and proliferative T-cell responses to insulin [62], thus suggesting that intranasal insulin induces mucosal tolerance. We propose that in intranasal protocols, peptides rather than protein should be administered.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, there has been some concern that induction of high autoantibody levels, following administration of autoantigens as immunomodulatory agents, could result in adverse events. In trials using either intranasal insulin in individuals at high risk for developing type 1 diabetes [22], or insulin B-chain given intramuscularly to patients with the disease [23], insulin antibodies were boosted without any adverse events. In LADA patients, GADA levels increased after injection of 500 µg GAD-alum but not after the lower dose, which yielded beneficial clinical effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the Intranasal Insulin Trial (INIT), phase I and II trials, a double-blind, crossover design was used to study Australian IAA-positive subjects to first-degree relatives with T1D. INIT-I was completed 2004 with no significant effect on ß-cell function but it showed some indications of immune tolerance to insulin 35 . INIT-II (NCT00336674) is an ongoing randomized; double-blind, placebo-controlled trial using nasal insulin (1.6 or 16 mg) and aims at assessing the effects of nasal insulin on islet autoimmunity.…”
Section: Nasal Insulinmentioning
confidence: 99%